Genetic basis of eco-geographic adaptation in wild relatives for wheat improvement - Adhikari, Elina (Kansas State University, 2020)
Wheat production has been improved significantly through plant breeding and agronomic practices. Nonetheless, the yield drive came with the cost of reduced genetic diversity in elite varieties. Bottleneck due to domestication, complexity in gene sharing due to polyploidization, loss of genetic diversity during hybridization, and years of selective breeding during commercialization narrowed the genetic base of the hexaploid wheat as compared to its wild counterparts. Availability of ancestral genomes in the wild relatives provides a fallback option for finding new allelic diversity required in wheat breeding. The wheat wild relatives are adapted to a wide range of climatic conditions. However, only a small fraction of the existing genetic diversity has been used in improving the adaptive potential of the hexaploid wheat. In my dissertation, I study how wheat evolved to adapt to its local climate using two immediate progenitors of wheat, Ae. tauschii and wild emmer wheat. In my first study, I used wild emmer, a tetraploid wild relative of the hexaploid wheat to study the genetics of clinal adaptation in wild emmer. The major objective of this study is to understand the role of geography and climate in shaping the allele frequency distributions indicating clinal adaptation. This study identifies the genomic signatures of adaptation and uses them for predicting adaptive potential. I use 444 geo-referenced wild emmer accessions collected throughout the wide climatic range of Israel. Genotyping is carried out using the 90K iSelect SNP array (90K) and the sequence-based genotyping (GBS) and is mapped to a wild emmer reference genome. The GBS and 90 K respectively identify 341,228 SNPs and 26,548 SNPs, among which, 26,697 SNPs and 9,175 SNPs are retained for respective genotyping platforms. The analysis of population stratification revealed four genetically distinct groups of wild emmer accessions largely reflecting their geographic distribution. Pearson correlation among 103 historical bioclimatic variables identifies twenty-five unique climatic variables that are noncollinear (Person correlation 0.85). Partitioning of genetic variance shows that geography and climate together explain 44% of genetic variations among emmer accessions with climatic factors accounting for 10% of the SNP variance. The eco-geographic adaptation alleles identified through environmental association scans of historical on-site climatic data improved the prediction accuracy of the heading date by 9%. This research finds that geography and climate play a vital role in shaping the genetic diversity of the wild emmer wheat. In my second study, I examine the environmental drivers guiding the clinal adaptation in Ae. tauschii, one of the diploid wild relative of wheat. A genome-wide environmental scan is used to identify the climate associated alleles (CAA) and select a representative set of 21 Ae. tauschii accessions enriched for CAAs. Using the top six Kansas adapted wheat varieties as recurrent parents and the selected Ae. tauschii accessions as donor parents, inter-specific population carrying introgression of the Ae. tauschii alleles in the D genome. Three hundred and fifty-one inter-specific BC1F3:5 lines developed through direct hybridization are used in studying the genomic pattern of alien introgression. Using 136 georeferenced Ae. tauschii accessions collected throughout the wide range of climatic conditions, I find that the Ae. tauschii broad lineages segregate with the eco-geographic climatic gradients. Out of 103 historical bioclimatic variables, twelve unique non-collinear climatic variables were identified. Climate, geography, and climate together with geography, respectively, explain 28%, 55%, and 65% of the SNPs variation. A genome-wide environmental scan identified a total of 508 CAAs, out of which 322 were successfully transferred into the Ae. tauschii-wheat inter-specific population. A separate analysis using the same data finds that hybrid sterility, reduced introgression in the pericentromeric regions, and reduced retention of the introgressed alleles in regions carrying domestication gene contribute to low retention of alien introgression in the inter-specific population. The field-based evaluation of 351 introgression lines in drought vs rainfed trials showed that 25 % of these lines outperform the best checks, implying successful introgression of beneficial variants positively affecting wheat performance under stress conditions. However, more in-depth analysis is required to understand the effect of these alien introgressions on wheat performance. Overall, my research demonstrates the tremendous potential of wild relatives’ genetic diversity for breeding climate-resilient wheat.
Keywords: Wheat improvement; Ae.tauschii Introgression; Genomewide scan; Population structure; Climate adaptation; Wild emmer